Effects of environmental enrichment on growth performance, physiological stress response and behaviour in broiler chickens - Mohd Tamagi, Nurhafizah (2019)
Chickens are constantly responding to environmental stimulation. These stimuli can be perceived as threatening or otherwise by birds. In view of this, environmental enrichment has been used as a tool to improve the welfare of intensively-raised farm animals. Experiment 1 was conducted to investigate the effects of auditory enrichment by means of classical music and Quran recitation, and regular human contact by means placing one hand inside the cage on growth performance, tonic immobility as an indicator of fear response and serum level of corticosterone (CORT) and ceruloplasmin (CPN) as physiological stress indicators in broiler chickens. A total of 768 day-old broiler chicks were subjected to the following treatments from day 1 to day 35 (i) no sound enrichment and without regular human contact, as control , (ii) no sound enrichment with regular human contact (HC), (iii) sound enrichment by classical music (Vivaldi’s Four Season) and without regular human contact (CM), (iv) sound enrichment by classical music with regular human contact (CMH), (v) sound enrichment by holy Quran recital (Yaseen chapter) without regular human contact (QR) and (vi) sound enrichment by holy Quran recital with regular human contact (QRH). Both sound stimuli were applied 3 hours a day intermittently. The regular human contact was conducted twice daily for 30 min between 10:30 h to 11:00 h, and 16:30 h to 17:00 h. For the regular human contact treatment, the experimenter entered the room gently with minimal noise and placed her right hand into the cage. There were no significant sound enrichment x human contact interactions for body weight (BW), feed intake (FI) and feed conversion ratio (FCR). The CM birds had significantly greater BW on days 7 and 14 and higher FI on day 7 than control birds. Regular human contact had no effect on BW, FI or FCR of birds. Both CM and QR birds had significantly lower CORT on day 7 and day 11, and also lower CPN on day 35 when compared to controls. Sound enrichment had a negligible effect on tonic immobility duration. These findings suggest that sound enrichment may improve early growth performance and reduce stress in broilers Experiment 2 was conducted to determine the effect of mirrors as enrichment on the welfare of broilers stocked at different densities. A total of 208 day-old Cobb chicks were randomly assigned to a 2 × 2 factorial arrangement, with or without mirrors and stocked at low or high densities. Implementation of mirrors in birds’ cage had no significant effect on growth performance and there was no interaction between stocking density and enrichment for BW, FI and FCR. However, the body weight and feed intake of birds stocked at high density (HD) was significantly lower than birds stocked at low density (LD) during day 35 of age. There were significant stocking density x enrichment interactions for CORT and CPN. While the presence of mirror panels in the cages of HD birds had no effect on CORT, it increased the CORT in LD birds. However, both HD and LD birds had lower CPN when mirror panel was present in their cages. Unlike the birds without mirrors, HD had no effect on CORT and CPN of the birds reared in cages with mirror enrichment. Stocking density and mirror enrichment only affected resting behaviour of birds. It is concluded that mirror panels are beneficial to reduce stress in chickens stocked at higher densities. Provision of mirrors did not give any negative effects on growth performance and behaviour of the chickens. In conclusion, environmental enrichment is more effective in reducing stress response rather than improving growth performance in broilers.